Alternate History: Playing with Contingency and Necessity - Singles, Kathleen (De Gruyter, 2013)
While, strictly speaking, Alternate Histories are not Future Narratives, their analysis can shed a clear light on why Future Narratives are so different from past narratives. Trying to have it both ways, most Alternate Histories subscribe to a conflicting set of beliefs concerning determinism and freedom of choice, contingency and necessity. For the very first time, Alternate Histories are here discussed against the backdrop of their Other, Future Narratives. The volume contains in-depth analyses of the classics of the genre.